Influence of World Development Indicators on Human Development: A Multiple Linear Regression and PSI Ranking Approach - Irvan, Irvan; Zahedi, Zahedi; Nusantara, Badai Charamsar; Romantica, Krishna Prafidya; Siswadi, Siswadi; Nasution, Marah Doly (ZERO: Jurnal Sains, Matematika dan Terapan, 2025)
This study investigates the influence of World Development Indicators (WDI)on the Human Development Index (HDI) within the regional context of Asiancountries. Understanding the interaction between these indicators and HDIholds strategic relevance for enhancing the formulation of evidence-baseddevelopment policies. The analysis focuses on five key indicators: populationgrowth, voice and accountability, government effectiveness, GDP per capitagrowth, and control of corruption. These variables represent essentialdimensions of governance and socioeconomic advancement. The datasetcomprises information from 46 Asian countries sourced from the World Bank.The methodological framework integrates multiple linear regression to evaluatethe magnitude of each variable’s contribution to HDI. The Preference SelectionIndex (PSI) is utilized to establish a performance-based ranking of countriesgrounded in the selected indicators. Results demonstrate that population growthand government effectiveness have significant impacts on HDI outcomes, whilethe remaining variables exhibit no statistically significant effects. Comparativeanalysis using PSI reveals inconsistencies between development indicator valuesand actual HDI positions. South Korea shows the highest consistency betweenquantitative rankings and HDI classification. These findings offer practicalinsights for policy prioritization by identifying the most influential determinantsof human development in the region. The study emphasizes the importance oftailored development strategies and encourages future research to strengthenmodel robustness through control variable inclusion, sensitivity analysis, andnon-linear modeling approaches.